Identification of the Extractives Chemical Compounds in Kiwi Residues by GC/MS Methods - Vaysi, Ramin (Asian Journal of Chemistry, 2011)
In this research, some chips of kiwi residues (Actinidia Spp.) From the west of Mazandaran in North of Iran were randomly chosen . At first wood flour and then measured extractive by TAPPI standard methods. The results of this study showed that average of extractives, cellulose, lignin and ash in Kiwi residues are 5.48, 36.75, 27 and 1.42 %, respectively. Then wood flour was washed by toluene-ethyl alcohol with the 2:1 ratio. To the extractives residue was added BSTFA reactor and samples kept in Ben Marry Bath in 70 ºC for 1 h and they were analyzed by GC/MS. For the identification of compounds were used GC diagram which shows abundance and retention time of each compound and calculation of quartz index and Adams table. The specified 14 compounds were present in Kiwi residues i.e., hexenol, isopropyl butyrate, phthalic acid, 2-methoxy pyrazine, ethylamine in high quantities.